Breastfeeding in the Context of Palliative Care. Issue 6 (November 2016) - Spatz, Diane L.
Abstract : Offering mothers options for breastfeeding should be part of a comprehensive perinatal palliative care program. Our breastfeeding expert, Dr. Spatz, describes how breastfeeding is integrated into the palliative care program at the Center for Fetal Diagnosis and Treatment at the Children's Hospital of Philadelphia where she is a nurse researcher and director of the lactation program.